2021
DOI: 10.1101/2021.06.29.450381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The MuvB Complex Binds and Stabilizes Nucleosomes Downstream of the Transcription Start Site of Cell-Cycle Dependent Genes

Abstract: The chromatin architecture in promoters is thought to regulate gene expression, but it remains uncertain how most transcription factors (TFs) impact nucleosome position. The MuvB TF complex regulates cell-cycle dependent gene-expression and is critical for differentiation and proliferation during development and cancer. MuvB can both positively and negatively regulate expression, but the structure of MuvB and its biochemical function are poorly understood. Here we determine the overall architecture of MuvB ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…However, the MuvB complex has a key role in DREAM-mediated repression. LIN37 is essential for DREAM-dependent gene repression, but its mode of action remains unknown [58,64,[112][113][114]. Interestingly, it is dispensable for the integrity of DREAM and transcriptional activation mediated by MMB:FOXM1 [58,64].…”
Section: Box 1 Mechanisms Of Transcriptional Repression By Dreammentioning
confidence: 99%
See 2 more Smart Citations
“…However, the MuvB complex has a key role in DREAM-mediated repression. LIN37 is essential for DREAM-dependent gene repression, but its mode of action remains unknown [58,64,[112][113][114]. Interestingly, it is dispensable for the integrity of DREAM and transcriptional activation mediated by MMB:FOXM1 [58,64].…”
Section: Box 1 Mechanisms Of Transcriptional Repression By Dreammentioning
confidence: 99%
“…Interestingly, it is dispensable for the integrity of DREAM and transcriptional activation mediated by MMB:FOXM1 [58,64]. LIN37 and RBBP4 interact with the N terminus of LIN9, while LIN54 and LIN52 bind to the C terminus of LIN9 [33,44,113] indicating that LIN9 forms a central scaffold within the MuvB core (see Figure 1 in the main text). Recent analyses showed that the LIN9 N terminus contacts RBBP4, creating a binding surface for LIN37.…”
Section: Box 1 Mechanisms Of Transcriptional Repression By Dreammentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA-binding domain of LIN54 recruits MuvB to its target genes at a specific sequence termed the cell cycle homology region (CHR) 7,8 . MuvB target promoters are TATA-less and the CHR is located directly upstream of the transcription start site (TSS) and the +1 nucleosome 8,9 . The presence of the +1 nucleosome generates a barrier for the assembly of the basal transcriptional apparatus 10 , and its positioning and dynamics are finely regulated to define the transcriptional status of each gene.…”
mentioning
confidence: 99%
“…Extensive biochemical analyses have demonstrated how the DREAM complex assembles on chromatin (Figure 1A) (LITOVCHICK et al 2007;PILKINTON et al 2007;SCHMIT et al 2007;GUILEY et al 2015;ASTHANA et al 2022). E2F-DP and LIN54, a MuvB component, direct site-specific chromatin localization (ZWICKER et al 1995;SCHMIT et al 2009;MULLER AND ENGELAND 2010;MULLER et al 2012;MARCEAU et al 2016).…”
Section: Introductionmentioning
confidence: 99%